The environmental sanitation knowledge related to the dengue hemorrhagic fever (DHF) incident in the coastal area of Mataram City, Indonesia: A cross-sectional study - Hendra Gustiawan; Sukardin Sukardin; Rahmani (Nurse Point: Journal of Nursing, 2025)
Background: Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus, transmitted by the Aedes aegypti mosquito. This illness poses a significant public health threat, particularly in tropical and subtropical regions such as Indonesia. Poor environmental sanitation can promote the breeding of the disease vector, leading to an increase in DHF cases. As a result, public awareness and understanding of sanitation practices are essential for preventing and controlling this disease. Purpose: This study aims to investigate the relationship between knowledge of environmental sanitation and the incidence of Dengue Fever in the coastal areas of Mataram City. Methods: This study adopted a quantitative approach with a cross-sectional design, collecting data at a singular point in time. A structured questionnaire was employed to observe and measure variables within the target population. Two hundred thirteen respondents were selected through systematic random sampling, adhering to clearly defined inclusion and exclusion criteria. The primary instruments utilized in this research included a survey sheet and a validated questionnaire. Results: The findings from the Spearman rank correlation test revealed a statistically significant relationship between environmental sanitation and the incidence of dengue hemorrhagic fever (DHF), as indicated by a p-value of 0.000 (p < 0.05). The correlation coefficient (r = 0.320) demonstrates a moderate positive association between these two variables. Conclusion and recommendation: This study reveals a statistically significant association between environmental sanitation conditions and the incidence of dengue hemorrhagic fever (DHF), indicating a moderate positive correlation (r = 0.320; p < 0.05). These findings underscore the importance of environmental hygiene as a crucial factor in the transmission dynamics of DHF within the population examined